Cell growth inhibition by sequence-specific RNA minihelices. - Hipps, D (1995)
RNA minihelices which reconstruct the 12 base pair acceptor-T psi C domains of transfer RNAs interact with their cognate tRNA synthetases. These substrates lack the anticodons of the genetic code and, therefore, cannot participate in steps of protein synthesis subsequent to aminoacylation. We report here that expression in Escherichia coli of either of two minihelices, each specific for a different amino acid, inhibited cell growth. Inhibition appears to be due to direct competition between the minihelix and its related tRNA for binding to their common synthetase. This competition, in turn, sharply lowers the pool of the specific charged tRNA for protein synthesis. Inhibition is relieved by single nucleotide changes which disrupt the minihelix-synthetase interaction. The results suggest that sequence-specific RNA minihelix substrates bind to cognate synthetases in vivo and can, in principle, act as cell growth regulators. Naturally occurring non-tRNA substrates for aminoacylation may serve a similar purpose.